El Señorío de la Gran Chinantla. Fronteras etnolingüísticas y conflictos agrarios en los siglos XVII-XVIII en la Sierra Norte de Oaxaca - De Teresa, Ana Paula (El Colegio de México, A.C., 2022)
The primary objective of this article is to contribute to the understanding of the sociodemographic, political and productive dynamics that fostered the struggle for the control of space among Indigenous settlements in the old district of Natividad Chinantla in Oaxaca at the end of the colonial era. It casts a critical gaze on anthropological and historical interpretations that ground ethnicity within the limits of territorial continuity, ignoring both the depopulation caused by the Conquest in Mesoamerica as well as the prolonged confrontations between Indigenous populations to encompass geographical areas through complex strategies that included alliances with different agents of the dominant colonial society. Based on the information available on the region and a review of agrarian and historical documents held by parishes and municipalities in the area under study, it seeks to sketch a map of the pattern of settlement and forms of access to land that prevailed at the end of the seventeenth century and beginning of the eighteenth in the province of Valle Nacional. This shows that, far from there being a historical continuity with the pre-Hispanic past, the Chinantec region registers a fluctuating dynamic, oscillating between expansion and territorial fragmentation.